2006
DOI: 10.1158/0008-5472.can-05-4441
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Tumor-binding Ligands in Cancer Patients with Phage Display Libraries

Abstract: Phage display has been used extensively in vitro and in animal models to generate ligands and to identify cancer-relevant targets. We report here the use of phage-display libraries in cancer patients to identify tumor-targeting ligands. Eight patients with stage IV cancer, including breast, melanoma, and pancreas, had phage-displayed random peptide or scFv library (1.6 Â 10 8 -1 Â 10 11 transducing units/kg) administered i.v.; tumors were excised after 30 minutes; and tumor-homing phage were recovered. In thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 47 publications
4
145
0
Order By: Relevance
“…delivery, and optical emission in NIR2 in a preclinical mouse model of ovarian cancer. Our acute toxicity studies are consistent with several other preliminary studies exploring the safety of M13 and SWNTs, in that a panel of serum biomarkers were not elevated (30)(31)(32)(33). Collectively, we believe these findings suggest that these materials warrant further consideration for clinical translation, which would include the development of instruments for real-time imaging, outcomes research such as survival studies in preclinical models, and rigorous safety evaluation through the National Characterization Laboratory (National Cancer Institute) and others to assess long-term trafficking and clearance of these materials as well as chronic toxicity studies.…”
Section: Discussionsupporting
confidence: 91%
“…delivery, and optical emission in NIR2 in a preclinical mouse model of ovarian cancer. Our acute toxicity studies are consistent with several other preliminary studies exploring the safety of M13 and SWNTs, in that a panel of serum biomarkers were not elevated (30)(31)(32)(33). Collectively, we believe these findings suggest that these materials warrant further consideration for clinical translation, which would include the development of instruments for real-time imaging, outcomes research such as survival studies in preclinical models, and rigorous safety evaluation through the National Characterization Laboratory (National Cancer Institute) and others to assess long-term trafficking and clearance of these materials as well as chronic toxicity studies.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo homing methodology has been expanded to select for phage clones that can extravasate from the vasculature and penetrate into tumors (Newton et al 2006), and for phage clones specific for atherosclerotic plaques (Kelly et al 2006b), among other tissue. Furthermore, in vivo homing has also been applied to human subjects (Arap et al 2002;Krag et al 2006). To refine in vivo homing protocols, a thorough biodistribution study with immunodeficient mice was performed, and circulation time was found to be a critical variable, depending on the organ or tissue being targeted (Zou et al 2004).…”
Section: Selections In Living Organismsmentioning
confidence: 99%
“…Results from several Phase I and II trials have been reported, and a number of trials are currently ongoing or at the stage of recruiting patients for trials. 63,[81][82][83][84] The results of clinical trials so far have been very encouraging, with reports of improved outcomes in terms of therapeutic efficacy, such as the absence of any dose-limiting toxicity and good tolerance of all peptide-targeted therapy combinations. 67 The most widely used peptides in the targeted-delivery applications are integrin-targeting RGD-peptides -the first tumor-targeting peptides discovered.…”
Section: Peptidesmentioning
confidence: 99%